Weight perceptions and health education on obesity among older adults - KIM, Seonghoon (Institutional Knowledge at Singapore Management University, 2022)
The current brief presents preliminary findings from a special module that measures perceptions of weight and receptivity to health education among older adults. Singapore Life Panel® (SLP) data collected in January 2022 (n=2814) were utilized. Two policy recommendations were made: The main findings highlight that weight misperception is prevalent among older adults. More than a third of respondents (39%) incorrectly perceive their weight status, particularly among overweight and obese older adults, as well as Malay and lower educated respondents. This suggests the importance of public health education for older adults to reduce misperceptions about their own over- and under-weight status, thereby promoting healthier behaviours and well-being in the long run. 2. In addition, the initial results indicate the well-being inequality by the willingness to learn about healthy lifestyles. The well-being gap is likely to become larger as those with a higher level of life satisfaction are more willing to take health education. This highlights the importance of focusing public health education and health awareness campaigns among disadvantaged populations.